Pelatihan dan Pengembangan Projek Penguatan Profil Pelajar Pancasila (P5) pada Kurikulum Merdeka di SD Negeri Unggulan 11 Pulau Morotai - Irawati Sabban; Risky Richlos Sarapung; Nurhani Mahmud (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The P5 training at SD Negeri Unggulan 11 Pulau Morotai aims to enhance teachers' understanding and skills in implementing the Pancasila Student Profile (P5) as part of the Kurikulum Merdeka. This training is designed with consideration for the region's limited access and understanding, covering three main aspects: P5 concept socialization, project design, and the implementation of P5 projects in schools. The program is conducted in two stages, namely project planning and implementation, followed by evaluation using quantitative and qualitative methods. The training results showed a significant improvement in participants' knowledge, with the average pretest score of 36.5 rising to 83 in the posttest. The first P5 project implemented was themed